2015
DOI: 10.1261/rna.053934.115
|View full text |Cite
|
Sign up to set email alerts
|

An extensive allelic series of Drosophila kae1 mutants reveals diverse and tissue-specific requirements for t6A biogenesis

Abstract: N 6 -threonylcarbamoyl-adenosine (t6A) is one of the few RNA modifications that is universally present in life. This modification occurs at high frequency at position 37 of most tRNAs that decode ANN codons, and stabilizes cognate anticodon-codon interactions. Nearly all genetic studies of the t6A pathway have focused on single-celled organisms. In this study, we report the isolation of an extensive allelic series in the Drosophila ortholog of the core t6A biosynthesis factor Kae1. kae1 hemizygous larvae exhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 56 publications
0
17
0
Order By: Relevance
“…Our group [12] and others [13] have observed that tcs3 mutants lacked imaginal discs and larval tissues were smaller, indicating that different cell types could have particular requirements for t 6 A-modified tRNAs; consistently Drosophila tcs3 [47] and human TCS3 /OSGEP [48] are differentially expressed in different tissues, supporting a tissue-specific demand. Accordingly, silencing the TCTC components in differentiated Drosophila photoreceptors did not cause any phenotype [13], suggesting that differentiated cells have a low demand for t 6 A-modified tRNAs; in contrast, highly proliferative cells such as the ones that the wing imaginal discs in Drosophila are composed, seem to have a high demand for these tRNAs.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…Our group [12] and others [13] have observed that tcs3 mutants lacked imaginal discs and larval tissues were smaller, indicating that different cell types could have particular requirements for t 6 A-modified tRNAs; consistently Drosophila tcs3 [47] and human TCS3 /OSGEP [48] are differentially expressed in different tissues, supporting a tissue-specific demand. Accordingly, silencing the TCTC components in differentiated Drosophila photoreceptors did not cause any phenotype [13], suggesting that differentiated cells have a low demand for t 6 A-modified tRNAs; in contrast, highly proliferative cells such as the ones that the wing imaginal discs in Drosophila are composed, seem to have a high demand for these tRNAs.…”
Section: Discussionmentioning
confidence: 72%
“…Accordingly, silencing the TCTC components in differentiated Drosophila photoreceptors did not cause any phenotype [13], suggesting that differentiated cells have a low demand for t 6 A-modified tRNAs; in contrast, highly proliferative cells such as the ones that the wing imaginal discs in Drosophila are composed, seem to have a high demand for these tRNAs. There could be a cell cycle-dependent requirement of t 6 A-modified tRNAs even in the same cell type, as we observed only G 0 /G 1 cells die by apoptosis, which is consistent with the severe target of rapamycin (TOR) inhibition in tcs3 mutants [12] as its activity promotes G 1 /S progression [49].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…elp3 is expressed ubiquitously, suggesting that the modification is present in most tissues but, since the knockdown phenotype affects certain cell types, there may be differential requirement for the mcm 5 s 2 U modification. This has been shown in the case of t 6 A; mutants that disrupt this modification present cell type specific phenotypes [46,47]. In addition, in absence of Elongator, translation of several specific mRNAs is affected [48] that may explain the tissue-or cell-type specific phenotypes.…”
Section: Discussionmentioning
confidence: 85%
“…We monitored the t6A modification at position 37 of tRNA‐Arg‐UCU and the ms2t6A modification at position 37 of tRNA‐Lys‐UUU (Figure a,b). Both the t6A and ms2t6A modifications can be monitored by primer extension assays using reverse transcriptase (RT) since the t6A modification leads to a partial block in RT extension while the ms2t6A leads to a strong block in RT (Clark, Evans, Dominissini, Zheng, & Pan, ; Lin et al, ). As expected, we detected RT pausing on the t6A modification in tRNA‐Arg‐UCU while RT was completely blocked for tRNA‐Lys‐UUU (Figure c,d).…”
Section: Resultsmentioning
confidence: 99%